Speaking anxiety among TVET undergraduates and its implication on graduate employability / Subatira Balakrishnan ... [et al.] - Balakrishnan, Subatira; Loke Abdullah, Loke Abdullah; Khoo, Linda Mei Sui; Thambu Raj, Joseph Alagiaraj (Universiti Teknologi MARA, 2025)
Speaking skill is an important predictor in graduate employability. Many job seekers suffer from speaking anxiety and this has affected their job employment opportunities. The focus of this research is to examine the TVET undergraduates’ speech anxiety level and determine what makes them apprehensive when speaking. The study also finds out the anxiety level differences between male and female TVET learners. The 313 research participants who answered McCroskey's Personal Report of Public Speaking Anxiety (PRPSA) questionnaire were undergraduates from a public technical university. The findings revealed that the learners had moderate levels of speech anxiety (M=115.7) and t-test results indicated that the mean scores for speaking anxiety levels of male and female learners did not differ in a way that was statistically significant though TVET female learners (M=113.30, SD =14.309) experienced slightly higher levels of speaking anxiety compared to their male counterparts (M=111.58, SD=15.996). The idea of giving a speech sent fears to the learners while losing concentration during speech heightened the learners’ speech anxiety level. Higher learning institutions could include public speaking trainings in their TVET syllabi. Additional soft skills such as public speaking helps ensure TVET graduates become industry priority in the employment market.